The Decade of Violence: A Comprehensive Analysis of Hate Crimes Against LGBTQ in Russia in the Era of the “Gay Propaganda Law” (2010–2020) - Katsuba, Sergey (Victims & offenders, 2024)
The research builds on the previous findings on the number of hate crimes against LGBTQ in Russia before and after the introduction of the so-called “gay propaganda law” in 2013 and significantly enriches them. The previous research studied hate crimes between 2010 and 2016 and was limited to using 2 databases of court decisions. The current research expands both the timeframe and the use of sources: it analyzes such crimes across 11 years (2010–2020) while adding 2 new databases of court rulings to achieve more comprehensive results and generate more accurate statistics of violent acts against LGBTQ in Russia. The previous research identified 263 cases of hate crimes, which was not sufficient to generate accurate statistics and indicated a trend only. The results of the current research significantly expand the existing knowledge by identifying 1056 hate crimes committed against 853 individuals including 365 fatalities. The greater number of cases enabled the current research to present a more thorough descriptive analysis of the crimes committed against LGBTQ in Russia. The paper introduces 3 main categories of hate crimes (Premeditated attacks, Not premeditated attacks, and the so-called “Gay panic defense” cases) and establishes that the number of cases when LGBTQ victim was purposefully selected and targeted grew substantially across the decade. The overall number of victims increased by three times after the introduction of the “gay propaganda law” in 2013 – from 34 in 2010 to 138 in 2015 and remained at relatively the same level for the remaining of the decade.